Lactate/ Albumin Ratio as Compared to Serum Lactate Levels as Mortality Indicator in Sepsis Patients - Javed, Hassan; Arshad, Abdul Rehman; Iqbal, Muhammad; Najam , Irfan; Uzair, Muhammad; Avais, Elleyyeen (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare lactate/ albumin ratio versus serum lactate levels as predictors of morbidity and mortality in sepsis patients. Study Design: Analytical cross-sectional study. Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Sep 2023 to Apr 2024. Methodology: This study was done on patients with a diagnosis of sepsis, while individuals with protein losing enteropathy, nephrotic syndrome, severe skin burns, recent history of albumin, and blood product transfusions were excluded. Demographic characteristics and investigations including serum lactate and albumin levels were recorded, and the primary outcome was the patient’s status post-hospital admission (remained alive and shifted toward or discharged) or died. Statistical significance was analyzed using receiver operating curve (ROC) analysis. Results: One hundred eight (n=108) patients with a median age of 55.33(38.25-70.00) years with male 62.00(57.41%) predominance were enrolled in this study. The median serum lactate and serum albumin levels at admission were 4.160 (2.95-6.40) mmol/L and 32.00 (27.00-37.75) g/L at the time of primary outcome. Lactate albumin ratio was 0.14(0.08-0.21). The receiver operating curve analysis for lactate showed area under curve 0.669 (95% confidence interval 0.563-0.776, p=0.003) while for lactate albumin ratio area under curve was 0.696 (95% confidence Interval 0.586-0.805, p=0.001). Conclusion: Serum lactate levels and lactate to albumin ratio both were significant and had a comparable profile in the prediction of morbidity and mortality of sepsis.